Analysis of the development of public-private partnership under the conditions of implementation of economic projects - Zakharina, Oksana (2020)
The basic goal of the state is to ensure a decent, stable and adequate standard of living for its citizens. In order to do this, the state forms a policy of development of various spheres and sectors of the economy. However, due to limited financial resources, the state is forced to seek new sources of economic projects in the country such as a platform for sustainable development of infrastructure, transport, energy and other industries. The purpose of the academic paper: investigation of advantages and disadvantages of PPP (public and private partnership) economic projects and analysis of key trends and sectoral direction of PPP development in different regions of the world. Results.